Education among Scheduled Caste Population in India - Harihar Sahoo; Sumana Acharya (Indonesian Journal of Geography, 2019)
Lack of education among the scheduled castes (SC) population in India may be the main reason for remaining at the lower end of the social structure. Therefore, this study attempts to explore the changing trends in literacy among the SC to find out the determinants of higher education and to explore the major reasons for never enrolling or discontinuing/dropping out from educational institutions among the SC population in India. Using the data from the Census of India and also from National Sample Survey and employing both bivariate and multivariate analysis, the results reveal that though there is an increasing trend in the literacy rate among the SC population, but the rates remain quite below the national average. Gender disparity in literacy is quite evident. The low level of higher education mainly due to reasons like failing in examinations, heavy drop-outs and stagnation caused by their poor socio-economic background. Despite various efforts by the central and state governments to eradicate differences in educational attainment among the social groups through several constitutional steps from time to time there still remain gaps to be bridged.